Synthesis and characterization of a novel 99mTc analogue of *I-mIBG showing affinity for nor-epinephrine transport positive tumors. Issue 69 (8th July 2016) - Sakhare, Navin; Das, Soumen; Mathur, Anupam; Mirapurkar, Shubhangi; Paradkar, Shalaka; Sarma, H. D.; Sachdev, S. S.
Abstract : 123 I/ 131 I labeled meta -iodobenzylguanidine ( m IBG) is a radiopharmaceutical used for diagnosis of neuroendocrine tumors (NET) related to neural crest origin. Present work evaluates a newly synthesized 99m Tc analogue of this radioiodinated derivative. Abstract : Radio-iodine ( 123 I/ 131 I) labeled meta -iodobenzylguanidine ( m IBG) is a proven radiopharmaceutical used for diagnosis of neuroendocrine tumors (NET) related to neural crest origin. Here, a 99m Tc analogue of *I- m IBG using 99m Tc-4+1 labeling approach has been synthesized and evaluated for its potential in NET imaging. This involved preparation of benzylguanidine precursor (mono-dentate donor) which was isolated in a five step synthetic procedure. The precursor was designed such that, in presence of a tetra-dentate NS3 co-ligand, [ 99m TcO4 ] − and Sn 2+ reducing agent, it formed the desired 99m Tc-4+1 complex. Complex formation was identified by radio-HPLC and structural details were affirmed by characterizing its rhenium analogue. Bio-evaluation studies of the complex were carried, both in vitro and in vivo, and the results obtained were compared with no-carrier added- 125 I- m IBG (nca- 125 I- m IBG). In vitro studies, in SK-N-SH neuroblastoma cell line showed affinity of the tracer towards nor-epinephrine transporters. Although the absolute uptake was lower compared to nca- 125 I- m IBG, its specificity was similar (∼90%) as the uptake reduced on inhibition with specific transport blocker, desmethylimipramine (DMI). Biodistribution studies in normal Wistar rats, pre-treated with m IBG and DMI, respectively, showed reduced myocardial uptake than its control. The results thus obtained merits high potential of synthesized 99m Tc-4+1 complex for NET imaging.